CLASSIFICATION OF REGIONAL TOURISM INDUSTRY DEVELOPMENT STRATEGIES AND THEIR CHRONOLOGY IN UZBEKISTAN - Yorqulov Muhammadmurod Ahmad ugli (Innovate Conferences, 2025)
The tourism industry has become one of the most significant sectors in the global economy, contributing to economic growth, job creation, and cultural exchange. In many regions around the world, tourism is considered a key driver for regional development, providing substantial benefits in terms of infrastructure development, local employment, and sustainable community development. The development of regional tourism requires a well-planned strategy, tailored to the specific characteristics, resources, and challenges of the region. By fostering sustainable growth, regional tourism strategies can enhance both the economic and social well-being of a community while preserving its cultural and environmental heritage. In the context of Uzbekistan, tourism has been identified as a critical sector for economic diversification and regional development. The country’s rich historical and cultural heritage, particularly along the ancient Silk Road, offers immense potential for tourism growth. The Government of Uzbekistan has recognized the strategic importance of tourism and has been actively working to position the country as an attractive tourist destination on the global stage. However, the successful development of regional tourism in Uzbekistan requires a comprehensive and tailored approach that takes into account the diverse characteristics of each region.